Pengetahuan pada Lansia mengenai Penyakit Rheumatoid Artritis di Wilayah Kerja Puskesmas Kalidoni Palembang - Yofa Anggriani Utama; Sutri Sari Sabrina Nainggolan (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Rheumatoid Arthritis in an autoimmne disease that requires long – term treatment and control. In thelast 15 years there have been many developments in the managemant of this disease so that the quality and life expectancy of Rheumatoid Arthritis patients has improved. The understanding that Rheumatoid Artritis is related to other comorbidities and early as possible so that it will improve short-term ang long- term result. The method of implementation is carried out offlinem at the orchid elderly posyandu in the Kalidoni Health Center Palembang by using the Health education method regarding Rheumatoid Artritis with leaflet.The implementation of the activity is carried out bay distributing the questionnaires about Rheumatoid Arthritis before counseling (pre-test) then distributing the questionnaires again. Questions about Rheumatoid Artritis after counseling (post-test). This activity was attended bay 30 erderly people. Based on the results of the activity, it was found that the level of knowlegde about before being given counseling was 8 participants (27%) participants had good knowlegde about Rheumatoid Arthritis. After being given health education, there was an increase in knowlegde as many 23 participants (77%) participants had good knowlegde about Rheumatoid Arthritis